L2 English vocabulary breadth and knowledge of derivational morphology: One or two constructs?. (April 2023) - Leontjev, Dmitri; Huhta, Ari; Tolvanen, Asko
Derivational morphology (DM) and how it can be assessed have been investigated relatively rarely in language learning and testing research. The goal of this study is to add to the understanding of the nature of DM knowledge, exploring whether and how it is separable from vocabulary breadth. Eight L2 (second or foreign language) English DM knowledge measures and three measures of the size of the English vocabulary were administered to 120 learners. We conducted two confirmatory factor analyses, one with one underlying factor and the other treating vocabulary breadth and DM as separate. As neither model had a satisfactory fit without introducing a residual covariance to the two-factor model, we conducted an exploratory factor analysis, which suggested two separate DM factors in addition to vocabulary breadth. Regardless, the analysis demonstrated that the DM knowledge was separate from learners' vocabulary breadth. However, learners' vocabulary breadth factor still explained a substantial amount of variance in learners' performance on DM measures. We discuss theoretical implications and implications for L2 assessment.